Staphylococcus aureus: significance, control and rapid detection across milk chain - Wandhare, Arundhati Ganesh; Singh, Anamika; Kaur, Jaspreet; Sihag, Manvesh Kumar; Dar, Rouf Ahmad; Singh, Kumar Siddharth; Panwar, Harsh; Gill, Jatinder Paul Singh (Indian Journal of Dairy Science, 2021)
Staphylococcus aureus is a major pathogen of public health concern with dominant role in food poisoning outbreaks, nosocomial and community-acquired infections, and also in bovine mastitis. Milk being a rich nutritious source for growth and proliferation of pathogenic species is prone to bacterial contamination, which can lead to spoilage and food poisoning. Toxin production, heat resistance, biofilm formation, antibiotic and lysozyme resistance are among the characteristics that contribute to S. aureus pathogenicity. S. aureus and its enterotoxins in food remains a daunting challenge, despite global efforts towards its mitigation. There is a need for rapid and cost-effective on-site detection of S. aureus in milk to prevent its transmission. The article outlines the significance of S. aureus in milk chain, its ability to adapt to environmental stresses, possible mitigation and rapid detection strategies; that may help to curtail its presence in milk chain and linked food poisoning episodes; besides ensuring food quality and consumer safety. Management of S. aureus and its multi drug resistant forms in milk chain will help to secure human and animal health, besides ensuring effective functioning of un-interrupted global food supply chain.